2019
DOI: 10.1161/strokeaha.118.023017
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Period Is a Risk Factor for Cerebral Venous Thrombosis

Abstract: Background and Purpose— Pregnancy and the postpartum period are generally considered to be risk factors for cerebral venous thrombosis (CVT), but no controlled studies have quantified the risk. Methods— Case-control study using data of consecutive adult patients with CVT from 5 academic hospitals and controls from the Dutch MEGA study (Multiple Environmental and Genetic Assessment of risk factors for venous thrombosis). Men, women over the age of 50, wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 6 publications
1
32
1
2
Order By: Relevance
“…It occurs three times more frequently in women, especially during pregnancy and with use of hormonal contraceptives, reaching up to 12 cases per one million deliveries 2 . Risk factors of CVT are different from that of ischemic stroke, with pregnant or postpartum women having 3.5 times higher risk of developing CVT than non-pregnant or postpartum women of similar age 3,4 . Recommended treatment of CVT is anticoagulation unless contraindicated, initially with intravenous unfractionated heparin (UFH) or low molecular weight heparin (LMWH) i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It occurs three times more frequently in women, especially during pregnancy and with use of hormonal contraceptives, reaching up to 12 cases per one million deliveries 2 . Risk factors of CVT are different from that of ischemic stroke, with pregnant or postpartum women having 3.5 times higher risk of developing CVT than non-pregnant or postpartum women of similar age 3,4 . Recommended treatment of CVT is anticoagulation unless contraindicated, initially with intravenous unfractionated heparin (UFH) or low molecular weight heparin (LMWH) i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the patient was at risk for development of CVT by presenting in the immediate postpartum period. A casecontrol study conducted by Silvis et al utilizing cases of CVT across 5 academic hospitals and controls from the Dutch MEGA study detected 41 cases of CVT diagnosed during pregnancy or postpartum (up to 12 weeks) and found that, when adjusted for pregnancy and the postpartum period, the highest attributable risk of development of CVT was during the first 6 weeks postpartum (adjusted odds ratio: 18.7; 95% CI: 8.3-41.9) and, surprisingly, little association 3 Case Reports in Obstetrics and Gynecology between pregnancy itself and CVT (adjusted odds ratio: 1.2; 95% CI: 0.6-2.3) [8]. Therefore, CVT should be strongly considered in the postpartum period for those with intractable headache, as this may confer a tenfold increased risk of CVT than nonpregnant or postpartum women of similar age.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the risk of CVT is also thought to be increased in those patients with sinusitis, thrombophilias, dehydration, head trauma, and pregnancy [6]. Pregnancy and postpartum status is conceivably one of the most common risk factors and misdiagnosis of CVT as an eclamptic seizure can be frequent [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Both pregnancy and the postpartum period have been widely considered to be common risk factors for CVT; however, recent studies have shown that a higher risk of CVT is associated with the postpartum period, and that pregnancy is not as significant. A multicenter, casecontrol study from the Netherlands in 2019, for instance, indicated that pregnancy did not increase the risk of CVT compared with the control group, while the risk of CVT was increased 10-fold during the postpartum period [21]. In addition, a large, multicenter clinical study (VENOST study) in Turkey involving 1144 patients in 2017 showed both that gynecologic risk factors constituted the largest group of causes of CVT, and that the postpartum period was the most prevalent of all gynecologic risk factors [22].…”
Section: Pregnancy and The Postpartum Periodmentioning
confidence: 99%